PENGARUH BRAND AMBASSADOR DAN KOREAN WAVE TERHADAP MINAT BELANJA ONLINE MELALUI MARKETPLACE TOKOPEDIA - Hendayana, Yayan; Afifah, Ni'matul (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2020)
This study aims to determine the effect of Brand Ambassador and Korean Wave on Online Shopping Interests. The study was conducted on regular students of the As-Syafi'iyah Islamic University and 96 respondents were obtained. Hypothesis testing uses validity and reliability tests. Normality test, multicolliniarity test and heterokedasticity test. The analysis conducted was regression and correlation analysis, coefficient of determination and t test. Based on the results of testing and discussion, partially Brand Ambassador has a positive and significant effect on Online Shopping Interests with a significance level of 0.006 <0.05 and tcount 2.089> 1.985. Partially Korean Wave has a positive and significant effect on Online Shopping Interests with a significance level of 0.015 <0.05 and tcount 2.384> 1.985. The coefficient of determination (R2) of 0.274 means that the percentage contribution of the influence of Brand Ambassador and Korean Wave to Online Shopping Interests is 27.4% and the remaining 72.6% comes from other variables not examined.